Diseño de estructura organizacional y control interno para la empresa aluminio arquitectónico Tunja SAS (2023)
The purpose of this research work is to make known the relevance and importance of the internal control system and the corporate image for all organizations, since they are a course of action for the achievement of the objectives, through processes and procedures defined to strengthen the efficiency and effectiveness of the same